Conductas prosociales y habilidades sociales en estudiantes de la Institución Educativa Inicial 60333 San Sebastián, Mariscal Ramón Castilla 2023 - Bravo Sanchez, Beronica Maribel (2024)
The purpose of the study was to determine the relationship that exists between prosocial behaviors and social skills in initial level students of the educational institution 60333 San Sebastián de Ramón Castilla. The study was guided by a basic quantitative approach of correlational scope and non-experimental transectional design. It included a sample population of 132 students, to whom the prosocial behavior scale and the social skills scale were applied. According to the results obtained, it has been established that the correlation between prosocial behaviors and social skills is notable and substantial, with a Kendall's Tau-B index of 0.654. Furthermore, a significant correlation is observed between the dimensions of helping (Kendall's Tau-B of 0,588), compassion (Kendall's Tau-B of 0.636), defense (Kendall's Tau-B of 0,689) and sharing (Kendall's Tau-B of 0.689). Kendall of 0,604) and social skills. It was concluded that, in the initial level students of the educational institution analyzed, there is a significant correlation between prosocial behaviors and social skills.